Clinicopathologic features and survival outcomes of ocular melanoma: a series of 31 cases from a tertiary university hospital - Selin Kestel; Feriha Pınar Uyar Göçün; Betül Öğüt; Özlem Erdem (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background We aimed to determine the effect of clinicopathologic features on overall survival among Caucasian ocular melanoma patients in the Central Anatolia region of Turkey. Methods This single-center study included conjunctival (n = 12) and uveal (n = 19) melanoma patients diagnosed between January 2008 and March 2020. Clinicopathologic features and outcomes were reviewed retrospectively. Five cases were tested for BRAF V600 mutations with real-time polymerase chain reaction, and one case was tested with next-generation sequencing. Survival was calculated using the Kaplan-Meier method. Results Thirty-one patients had a mean initial age of 58.32 years (median, 61 years; range 25 to 78 years). There were 13 male and 18 female patients. The median follow-up time was 43.5 months (range, 6 to 155 months) for conjunctival melanoma and 35 months (range, 8 to 151 months) for uveal melanoma. When this study ended, eight of the 12 conjunctival melanoma patients (66.7%) and nine of the 19 uveal melanoma patients (47.4%) had died. The presence of tumor-infiltrating lymphocytes was related to improved overall survival in conjunctival melanoma (p = .014), whereas the presence of ulceration (p = .030), lymphovascular invasion (p = .051), tumor in the left eye (p = .012), tumor thickness of > 2 mm (p = .012), and mitotic count of >1/mm2 (p = .012) reduced the overall survival in conjunctival melanoma. Uveal melanoma tumors with the largest diameter of 9.1-15 mm led to the lowest overall survival among subgroups (p = .035). Involvement of the conjunctiva (p=.005) and lens (p = .003) diminished overall survival in uveal melanoma. BRAF V600 mutation was present in one case of conjunctival melanoma, GNAQ R183Q mutation was present in one case of uveal melanoma. Patients with uveal melanoma presented with an advanced pathological tumor stage compared to those with conjunctival melanoma (p = .019). Conclusions This study confirmed the presence of tumor-infiltrating lymphocytes as a favorable factor in conjunctival melanoma and conjunctival and lens involvement as unfavorable prognostic factors in uveal melanoma for overall survival, respectively.